Reframing the Lampedusa Cross: The British Museum’s Display of the Mediterranean Migrant Crisis - Breene, Morgan Lynn (Journal of Contemporary Archaeology, 2017)
In the fall of 2015, the British Museum acquired the Lampedusa Cross, a cross of the Latin type crafted from wood salvaged from a migrant vessel which wrecked off of the coast of Lampedusa in 2013, killing nearly two thirds of the 566 people on board. The Musuem has displayed the object since December 2015 as a testament to the ongoing Mediterranean migrant crisis and a physical manifestation of the “suffering and hope” experienced by those making the journey. Questions must be raised however, about the appropriateness of this particular object as representative of the crisis and whether it obscures, rather than promotes, the experiences of migrants and the European response to their plight.